Focus Group Discussion (FGD) on the potential of green procurement in Sarawak Construction Industry - Mohamad Bohari, Asmah Alia (UiTM Sarawak, 2018)
A group of researchers from Fakulti Senibina, Perancangan & Ukur, UiTM Sarawak successfully organised a half-day focus group discussion on the potential of green procurement in Sarawak construction industry on 6 February 2018 at Merdeka Palace Hotel. This discussion aimed to introduce the new procurement approach that integrates the green practices in the construction project delivery and gauge the participants’ opinion on the potential and barriers of the green procurement implementation within the Sarawak Construction Industry. The FGD involving’^3 .participants included subject matter experts, academicians and industry practitioners.